Plant extracts: Nanoparticle sources - Gaanty Pragas, Maniam; Natanamurugaraj, Govindan; Mohd Hasbi, Ab. Rahim; Mashitah, Mohd Yusoff (Elsevier, 2020)
Nanoparticles (NPs) (usually in dimensions of 1–100 nm) have been proven, through numerous research findings, to have excellent properties in term of physiochemical, antifungal, chemical, catalytic, thermal conduction, mechanical, electrical, optical, and many more [1,2]. NPs have vital roles in agro-production and protecting crops from diseases, both directly and indirectly, and they go even further to influence the soil microbial population. At the nanoscale, the elementary understanding of chemical and physical properties is very distinctive. As such, research outputs at different scales will have different interpretations that in turn radiate different properties, even for the same element. Owing to the superior qualities of NPs, research on them is intense, as many researchers are intensively working in the area. Nanoparticle utilization is glaring in many areas, including healthcare and cosmetics, food and feed, drug delivery systems, the space industry, electronics, optoelectronics, biomedical science, and many more [3,4].